Characterization and qualitative changes in DOM chemical characteristics related to hydrologic conditions in a Pampean stream - Messetta, María Laura (2017)
The aim of our study was; (i) to characterize the composition of DOM in stream water and their potential sources (groundwater, overland flow, subsurface flow and rain water) and (ii) to analyze changes in DOM concentration and compositionunder different hydrological conditions (baseflow and high flow) in a third-order Pampean stream (Argentina). Pampean streams are mainly fed by the shallow aquifer under baseflow conditions and they lack of riparian forest. In addition, water velocity islow due to the gentle slope of the region and nutrient levels are high, favoring the development of rich macrophyte communities. DOM optical properties in the stream and end members were determined by combining bsorbance-fluorescence spectroscopy techniques. Our results indicated that DOM chemicalcharacteristics in the stream were mainly modulated by a differential ntribution of end members to stream water depending on hydrological conditions. We observed that DOM in groundwater showed a microbial origin while DOM in runoff was terrestrially-derived. DOC concentration and inputs of humic substances from the riparian zone increased with discharge at high flow conditions. Due to the strong link between DOC properties and the riparian environment, structural alterations in the stream channel and changes in riparian vegetation (forestation) may result in changes in DOM composition and dynamics.